Improvisation and Music Education: From the Sonic to Social Attunement - Vanja Dabic (Universitas Gadjah Mada, 2021)
In order to create a relationship to music, artists first need to create a relationship with their inner sound, and the way in which they approach the manifestation of sound from their instrument (whether it'd be through the use of hands, voice, or a plain manifestation of thoughts). Since this process is dialectic in its nature, the ability to develop this type of responsiveness, sometimes referred to as